Ultrasound can detect alternating vertebral artery occlusions due to hangman fracture. Issue 4 (24th March 2020) - Ohara, Keiichiro; Sato, Takeo; Mitsumura, Hidetaka; Arai, Ayumi; Komatsu, Teppei; Sakai, Kenichiro; Kawamura, Daichi; Ohashi, Hiroki; Ishibashi, Toshihiro; Murayama, Yuichi; Iguchi, Yasuyuki
Abstract: We present a case of alternating vertebral artery occlusions due to hangman fracture which was detected by repeated ultrasound. An 89‐year‐old woman presented with sudden onset of consciousness disturbance. Magnetic resonance imaging showed bilateral cerebellar ischemic lesions and daily alternating vertebral artery occlusions. Carotid ultrasonography and transcranial color flow imaging showed blood flow changes from day to day which indicated an abnormal hemodynamic status of bilateral vertebral artery. Computed tomography angiography revealed hangman fracture and severe compression of bilateral vertebral artery with thrombi. We applied Halo‐Vest fixation and started the patient on anticoagulation therapy. Then, carotid ultrasonography and transcranial color flow imaging demonstrated improvement of bilateral vertebral artery blood flow. The patient remained free of neurological deficits after Halo‐Vest fixation and anticoagulation. This case highlights the importance of repeated ultrasonographic evaluation of cerebral arteries in patients with ischemic stroke by hangman fracture.